Extremozymes and their industrial applications - Agnihotri, Shekhar; Arora, Naveen Kumar; Mishra, Jitendra (Cambridge, Massachusetts Academic Press, 2022)
"Extremophiles belong to members of all three domains of life, i.e., bacteria, archaea, and eukarya. However, a high proportion of extremophiles are archaea and bacteria. These microbes live under chemical and physical extremes that are usually lethal to cellular molecules, yet they not only manage to survive but even thrive in such conditions. Extremophiles have important practical and industrial uses. They are a valuable source of industrially important enzymes also known as extremozymes. Recent research has revealed that extremozymes have unique structural features essential for biocatalysis under extreme conditions. Extremozymes have great commercial values and are known for their potential use in biotechnology, biomining, and bioremediation. Extremozymes and their Industrial Applications highlights the current and topical areas of research in this rapidly growing field of extremophiles and their applications. Expert researchers from around the globe are trying to uncover the underlying mechanisms responsible for their specific adaptations under extreme environments. The topics covered include the ability of acidophiles to maintain a neutral intracellular pH, the way psychrophiles "loosen up" their proteins at low temperatures, and other equally ingenious adaptations and metabolic strategies that extremophiles use to survive and flourish under extreme conditions. Extremozymes and their Industrial Applications also covers the established biotechnological uses of extremophiles and the most recent and novel applications, including their exploitation for enzyme production. Potential use of extremophiles and their enzymes in the generation of sustainable energy, biomass conversion, agro-waste processing, and biocontrol of phytopathogens is also covered. The book will be very useful for researchers and students working in the area of industrial microbiology and biotechnology, and microbial ecologists. It is also recommended reference text for those interested in the biochemistry and microbiology of extremophiles, as well as for those interested in bioprospecting, biomining, biofuels, and biodegradation."
Includes bibliographical references and index.
Keywords: Biocatalysis -- Industrial applications; Biotechnology -- Industrial applications; Enzymes -- Industrial applications; Extreme environments -- Microbiology; Microbial ecology -- Research